JAVANESE WOMEN’ PATRIOTISM IN THE KETOPRAK MANUSCRIPT “KYAI KALA GUMARANG” - Anton Kurniawan; Suyitno Suyitno; Ani Rakhmawati (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
The purpose of this study is to describe Javanese women’s patriotism in the ketoprak manuscript “Kyai Kala Gumarang”. This qualitative descriptive study used a content analysis technique to analyze the data. The main data source was the ketoprak manuscript titled “Kyai Kala Gumarang”. Library research methods were employed to collect the data. Data analysis techniques using interwoven analysis techniques and interactive analysis with a feminist approach. The results of the study showed that the words, phrases, and sentences in the manuscript indicated that women had a key role as an important messenger of the kingdom, as a distraction, and as soldiers defending the homeland.